2021
DOI: 10.1093/geront/gnab177
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Loneliness With Health and Social Care Utilization in Older Adults in the General Population: A Systematic Review

Abstract: Background and Objectives Loneliness is proposed to be linked with increased service use. This review examined the association of loneliness and health and social care utilisation (HSCU) in older adults from the general population. Research Design and Methods Four databases were screened for studies that examined the association of loneliness (predictor) with HSCU (outcome) in older adults (defined as majority of sample 60 or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 54 publications
(104 reference statements)
1
10
0
Order By: Relevance
“…With regard to enabling resources, it appears quite counterintuitive that lower loneliness levels are associated with higher GP visits in our study because we initially assumed that GP visits may substitute missing social contacts (even during the pandemic). However, a recent systematic review also concluded that there is inconclusive evidence regarding the association between loneliness and outpatient physician visits [ 23 ]. Possible explanations for the association identified in our study may refer to the fact that individuals with higher loneliness levels may become phlegmatic (in terms of visiting the GP), whereas individuals with lower loneliness levels may be physically active and may have quite frequent preventive visits to the GP [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…With regard to enabling resources, it appears quite counterintuitive that lower loneliness levels are associated with higher GP visits in our study because we initially assumed that GP visits may substitute missing social contacts (even during the pandemic). However, a recent systematic review also concluded that there is inconclusive evidence regarding the association between loneliness and outpatient physician visits [ 23 ]. Possible explanations for the association identified in our study may refer to the fact that individuals with higher loneliness levels may become phlegmatic (in terms of visiting the GP), whereas individuals with lower loneliness levels may be physically active and may have quite frequent preventive visits to the GP [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Loneliness was associated with increased likelihood of unmet healthcare needs in the previous 12 months, adjusted for various predisposing, enabling and need factors. While research on loneliness and healthcare utilisation is mixed and has methodological limitations,24 45 findings suggest that compared with those who are not lonely, lonely individuals are more likely to use certain types of health services, such as more frequent emergency department visits and more visits to general practitioners 19 26. Researchers examining loneliness and visits to primary care providers have found that those who are lonely have a greater number of visits to providers than those who are not lonely 25.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, those who are lonely may exhibit avoidant behaviours, increasing likelihood of unmet needs 18. Research suggests that loneliness is somehow associated with increased use of health services such as more emergency department use and general practitioner visits; however, the evidence is mixed and the quality of studies varies due to differences in operational definitions, measurement, study samples and cross-sectional study designs 19–24. The results of these studies found that being lonely, as opposed to not lonely, may be associated with greater use of certain types of health services.…”
Section: Introductionmentioning
confidence: 99%
“…Nonpsychotic mood and anxiety disorders, and other mental illnesses (psychoses, personality disorders, substance abuse) were included in the list of 18 conditions used to define multimorbidity (full list in Supplementary Table S3). 37 Covariates were selected because of their association with loneliness and healthcare use, based on prior research 38 . Age, sex, rurality, neighborhood income quintile, and multimorbidity were obtained from administrative data sources, while other covariates were self‐reported by respondents in the CCHS.…”
Section: Methodsmentioning
confidence: 99%
“…37 Covariates were selected because of their association with loneliness and healthcare use, based on prior research. 38 Age, sex, rurality, neighborhood income quintile, and multimorbidity were obtained from administrative data sources, while other covariates were selfreported by respondents in the CCHS. The source of data for sex in our study is self-report (with male or female options) at the time of health insurance registration; gender identity was not captured in either health administrative data nor in the CCHS-HA.…”
Section: Covariatesmentioning
confidence: 99%